PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN PENDIDIKAN PANCASILA SISWA KELAS III SD NEGERI 31 LUBUKLINGGAU - Swari, Dita Nurindah; Asep Sukenda Egok; Willy Lontoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the application of the Cooperative Learning model of the Student Teams Achievement Division (STAD) type in Pancasila Education for third-grade students at SD Negeri 31 Lubuklinggau in the 2024/2025 academic year. The research method used was quantitative with a pre-experimental design, specifically the one-group pre-test-post-test model. Based on data analysis results, the average pre-test score of students was 41.42, with no students achieving the minimum mastery criteria. After the implementation of the STAD cooperative learning model, the average post-test score increased to 87.5, with 21 out of 24 students achieving mastery. Hypothesis testing using the Z-test showed that Z count > Ztable (4.22 > 1.64), indicating that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the application of the STAD-type cooperative learning model has a significant effect on improving the learning outcomes of Pancasila Education for third-grade students at SD Negeri 31 Lubuklinggau.